PELAKSANAAN FUNGSI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) LUHAK NAN TUO DALAM PENANGANAN KEKERASAN SEKSUAL DI KABUPATEN TANAH DATAR TAHUN 2015-2018 DI PROVINSI RIAU TAHUN 2018-2019 - Khairul Havif; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Law Number 23/2014 concerning Local Government, mandates in article 12 paragraph (2) point b that there is mandatory government affairs that are not related to basic services namely the empowerment of women and children. Today the social phenomenon that afflicts women and children is quite concerning. Every year there is an increase in cases of women and children in Indonesia, as is the case in Tanah Datar Regency. The local government is seriously concerned about the case of sexual abuse through the Social Service for Women Empowerment and Child Protection and P2TP2A. In the Implementation of Its Functions P2TP2A Luhak Nan Tuo has 5 areas of service functions namely The Field of Complaint Services, Health Rehabilitation Services, Social Rehabilitation Services, and Social Reintegration, Legal Assistance and Advocacy Services and Administrative, Data, Information and Reporting Services.This research aims to find out the implementation of the function of the Integrated Service Center for The Empowerment of Women and Children (P2TP2A) in the treatment of sexual violence in Tanah Datar Regency as well as to know the inhibitory factors in the implementation of the function of the Integrated Service Center for The Empowerment of Women and Children. The research site is in Tanah Datar Regency at the PPPA Social Service office of Tanah Datar Regency and The Integrated Service Center for The Empowerment of Women and Children (P2TP2A) Luhak Nan Tuo. This research uses a qualitative approach. This type of research is descriptive. Data is collected through informants purposively. Data collection techniques uses interviews and documentation.The result of this study is that the Implementation of Service Function of the Integrated Center for The Empowerment of Women and Children in the handling of sexual violence has not been optimally implemented. This is due to several factors such as lack of facilities and infrastructure, lack of coaching and training of P2TP2A employees in carrying out activities and long service time. Keywords : P2TP2A, Sexual Violence, Function Execution, Public Service